Reduction of Faddeev equations to the system of equations for functions of one variable by hyperspherical harmonics method - V. K. Tartakovsky; I. V. Kozlovsky; V. I. Kovalchuk (Ядерна фізика та енергетика)
After reformulating of Faddeev equations and its reducing to the equation with one complete wave function the most complex part of this function is represented in the form of rapidly converging series on K-harmonics. The system of the connected integral equations is constructing for radial functions of the collective variable and the procedure of its solution is proposed.